Neoadjuvant Chemotherapy for Larynx Preservation: Has it Lost Importance? - Benson, Rony; Mallick, Supriya; Rath, G K (Indian Journal of Medical and Paediatric Oncology, 2018)
Over the time, the aim of treatment for locally advanced laryngeal and hypopharyngeal carcinoma has changed from cure to cure with the functional larynx. Chemoradiation has emerged as the most important therapeutic modality for patients with locally advanced disease. However, systemic failure remains an important area of concern. Induction chemotherapy has emerged as promising organ preservation approach as it gives an window to select responders and continuing treatment with nonsurgical approach as well as reduces systemic recurrence and improve survival with a functional larynx. However, there are questions about the efficacy of this approach. In this context, we aim to evaluate the trials for locally advanced laryngeal and hypopharyngeal cancer attempting to optimize therapeutic outcome with addition of induction chemotherapy. This present review intends to look into the therapeutic ratio of induction chemotherapy for disease control, organ preservation.
Keywords: Chemoradiotherapy; induction chemotherapy; larynx preservation; locally advanced laryngeal carcinoma; squamous cell carcinoma